2020
DOI: 10.1007/s10147-020-01727-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the concordance in HPV type between self- and physician-collected samples using a brush-based device and a PCR-based HPV DNA test in Japanese referred patients with abnormal cytology or HPV infection

Abstract: Background To adopt HPV self-sampling in Japan, we assessed the concordance between self- and physician-collected human papillomavirus (HPV) samples from Japanese patients and examined the performance of HPV self-sampling for cervical intraepithelial neoplasia grade 2 or worse (CIN2+). Methods Patients who had previously tested negative for intraepithelial lesions or malignancy/HPV-positive, and patients with atypical squamous cells of undetermined significance or worse (ASCUS+) cytology were eligible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…In our study, the sensitivity of self-collected samples for HPV-16 (85.5%) was higher than 75%, and the specificity (97.9%) was comparable to the 100% reported in a previous study [ 13 ]. The sensitivity and specificity for the other 12 hr-HPVs in the current study were similar to that previously reported in Japan [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the sensitivity of self-collected samples for HPV-16 (85.5%) was higher than 75%, and the specificity (97.9%) was comparable to the 100% reported in a previous study [ 13 ]. The sensitivity and specificity for the other 12 hr-HPVs in the current study were similar to that previously reported in Japan [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, studies comparing the detection rate of HPV between healthcare worker-collected-and self-collected samples in LMICs are limited. Moreover, the majority of studies have focused on comparing healthcare workercollected and self-collected samples for HPV DNA detection [7,8,[24][25][26] than HPV mRNA detection. This study aimed to compare the positivity of hrHPV DNA and hrHPV mRNA between healthcare workercollected and self-collected samples and investigate the accuracy of the applicator-tampon-based self-collected samples in detecting hrHPV DNA and hrHPV mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The shortage of gynecologists would be one of the causes impairing the participation rate, particularly in rural areas [13]. Though self-sampling kits demonstrated highly acceptable performance in usage and sensitivity, these were not widely accepted due to the need to use special equipment and the resistance of women to put the equipment into the vagina themselves in Japan [8,9]. The urine hrHPV-DNA test could be a substitute for the cervical test and is expected to increase receiving rate in the uterine cervical cancer screening because that does not need a special sampling kit, examination chair, or gynecologist examination.…”
Section: Discussionmentioning
confidence: 99%
“…The HPV-DNA test using a urine sample is expected to substitute the cervical test by including self-sampling because it is easier for examinees to Diagnostics 2021, 11, 1895 2 of 9 collect specimens themselves, there is no need to prepare examination beds and expensive collection kits, and it has an advantage in preventing coronavirus transmission by reducing contact with the medical staff during the recent COVID-19 pandemic. Several reports have shown the good concordance between urine and cervical sampling to detect HPV infection in women with cervical intraepithelial neoplasia (CIN) [5][6][7][8][9]. Daponte et al reviewed the literature and introduced a urine HPV test as a most promising tool to change cervical cancer prevention strategies [10].…”
Section: Introductionmentioning
confidence: 99%